Phase-pure formamidinium lead iodide perovskite films deposited via flow-limited field-injection electrostatic spraying - Riley Vesto; Matthew Pianfetti; Griffin Rzonca; Frank Kelly; Rebekah Wilson; Hyungsoo Choi; Kyekyoon Kim (AIP Advances, 2025)
Phase-pure perovskite formamidinium lead iodide (FPI) films were deposited using flow-limited field-injection electrostatic spraying at a deposition temperature of 120 °C without employing stabilizing additives while retaining large-area scalability. The structures of the films were analyzed using the Rietveld refinement of x-ray diffraction measurements, enabling achievement of phase purity under optimized charging voltage and deposition temperature. The effect of precursor molar ratio on the phase of FPI was investigated by Fourier transform infrared spectroscopy, revealing the crucial role of the FAPbI3 · DMSO adduct formed in solution for achieving phase purity. Optical properties and photoactivity were assessed by absorption spectroscopy and time-resolved photoluminescence, demonstrating viability for application to solar cells.